Transformation of Educational Technology through Training to Increase Teacher Competency in Designing Innovative Learning Media - Indri Astuti; Aloysius Mering; Masriani Masriani; Toyib Bikoir (Universitas Tanjungpura, 2021)
The purpose of community service activities (PKM) carried out by Master of Educational Technology students at Tanjungpura University Pontianak is to provide guidance related to the transformation of educational technology to improve teacher competence in designing innovative learning media. Participants in community service activities (PKM) are kindergarten, elementary, junior high, high school teachers in Teluk Batang sub-district, North Kayong Regency. This activity is carried out using the ADDIE development model and technical activities combined, namely online by utilizing the Google Meet application as a virtual face-to-face room in delivering material related to technological transformation in the world of education, and the offline model is carried out with guidance directly to the participants of the activity face-to-face. The result of this activity is a change in teacher competence in designing innovative technology-based learning media by utilizing the Camtasia application. Teachers use the Camtasia application to create innovative learning media in the form of learning videos adapted to teaching materials in learning.